Bilaminar Mechanics of the Human Optic Nerve Sheath. (2nd July 2020) - Shin, Andrew; Park, Joseph; Le, Alan; Poukens, Vadims; Demer, Joseph L.
ABSTRACT: Purpose/Aim: The adult human optic nerve (ON) sheath has recently been recognized to be bilaminar, consisting of inner layer (IL) and outer layer (OL). Since the ON and sheath exert tension on the globe in large angle adduction as these structures transmit reaction force of the medial rectus muscle to the globe, this study investigated the laminar biomechanics of the human ON sheath. Materials and Methods: Biomechanical characterization was performed in ON sheath specimens from 12 pairs of fresh, post-mortem adult eyes. Some ON sheath specimens were tested completely, while others were separated into IL and OL. Uniaxial tensile loading under physiological temperature and humidity was used to characterize a linear approximation as Young's modulus, and hyperelastic non-linear behavior using the formulation of Ogden. Micro-indentation was performed by imposing small compressive deformations with small, hard spheres. Specimens of the same sheaths were paraffin embedded, sectioned at 10 micron thickness, and stained with van Gieson's stain for anatomical correlation. Results: Mean (± standard error of the mean, SEM) tensile Young's modulus of the inner sheath at 19.8 ± 1.6 MPa significantly exceeded that for OL at 9.7 ± 1.2 MPa; the whole sheath showed intermediate modulus of 15.4 ± 1.1 MPa. Under compression, the inner sheath was stiffer (7.9 ± 0.5 vs 5.2 ± 0.5 kPa) and more viscous (150.8 ± 10.6 vs 75.6 ± 6 kPa s) than outer sheath. The inner sheath had denser elastin fibers than outer sheath, correlating with greater stiffness. Conclusions: We conclude that maximum tensile stiffness occurs in the elastin-rich ON sheath IL that inserts near the lamina cribrosa where tension in the sheath exerted during adduction tethering may be concentrated adjacent the ON head.